Enlightenment on Unani Concept of Ghiza (Diet) in Modern Perspective. - Fahamiya, N.; Shiffa, M.S.M.; Farzana, M.U.Z.N. (Faculty of Indigenous Medicine, University of Colombo, 2015)
Unani healing system employs a holistic approach in prevention and treatment of diseases...
Keywords: Functional food; nutraceuticals; Ghiza; Asbab-e-Sitta-e-Zaroriayah